The Implementation of Religious Education in Asuhan Kasih Special Elementary School in City of Kupang East Nusa Tenggara - Ali Khudrin (Analisa: Journal of Social Science and Religion, 2012)
Research on the Implementation of Religion Education was held at the special Ele- mentary School (SDLB) “Asuhan Kasih” in Kupang, East Nusa Tenggara Province. The results of this study indicate that the implementation of religion education at Orphanage SDLB “Asuhan Kasih” can run well. Despite this aspect of the teaching force is still not in accordance with the subjects being taught. It can be seen from a qualified religion teacher not as a religious teacher. Contributing factor in the lear- ning process is the higher spirit of in learning religion, dedication of religion teacher, the availability of classroom space, facilities and location are not far from the school environment for learners. Inhibiting factor in the learning process is the absence of special teachers to teach religious education, lack of teaching aids, lack of reference books, and a lack of operational funds.